Sosialisasi Mitigasi Bencana Daerah Pesisir Bagi Siswa SD Negeri Rutong - Yoisye Lopulalan; Godwin W. A. Hehanussa; Hendra Titawael; Sherly Lewerissa; Marlin C. Wattimena; Laury M. Ch. Huwae; Ronald D. Hukubun (Lembaga Pengembangan Kinerja Dosen, 2023)
Disaster mitigation is an effort to reduce casualties and provide a proper and good understanding to the public regarding natural disasters. This activity aims to provide early insight and knowledge regarding natural disasters. The method of implementing this community service uses the socialization method with Rutong State Elementary School students as participants. This socialization material focuses on mitigating the tsunami and earthquake disasters, a major threat to Rutong Village, located in a coastal area.